Development of a Novel Intra-Abdominal Pressure Transducer for Large Scale Clinical Studies - Niederauer, Stefan (Biomed Microdevices, 2017)
Intra-abdominal pressure may be one of the few modifiable risk factors associated with developing a pelvic floor disorder. With one in eight women having surgery to correct a pelvic floor disorder in their lifetimes, intra-abdominal pressure may be a key to understanding the disease etiology and how to mitigate its occurrence and progression. Many traditional methods of intra-abdominal pressure measurement have limitations in data quality, environment of use, and patient comfort. We have modified a previously reported intravaginal pressure transducer that has been shown to overcome other intra-abdominal pressure measurement technique limitations (Coleman 2012). Our modifications to the intravaginal pressure transducer make it easier to use, less costly, and more reliable than previous designs, while maintaining accuracy, integrity, and quality of data. This device has been used in over 400 participants to date as part of one of the most comprehensive studies examining the relationship between intra-abdominal pressure and pelvic floor disorders.